2018
DOI: 10.1002/ccd.27718
|View full text |Cite
|
Sign up to set email alerts
|

In vitro flow and optical coherence tomography comparison of two bailout techniques after failed provisional stenting for bifurcation percutaneous coronary interventions

Abstract: Objectives To evaluate, in vitro, SB stenting techniques after failed provisional stenting. We aimed to compare flows and stent strut apposition of T and protrusion (TAP) versus Reversed String (RS) techniques using a flow simulator, optical coherence tomography (OCT) using silicon bifurcation phantoms with different bifurcation angulations. Background While bifurcation coronary artery stenoses are preferably treated with provisional T‐stenting strategy, the preferred bailout two stents technique to treat the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One concern about this simplified protocol is that retrieval of the jailed balloon might leave a "gap" (malapposition) between the struts and vessel wall. A previous study showed that OCT could conveniently be acquired from silicon bifurcation phantoms, and OCT had quite strong resolution power to recognize malapposition (27). Therefore, this silicon bifurcation phantom is suitable for testing the reliability of the simplified protocol.…”
Section: Discussionmentioning
confidence: 99%
“…One concern about this simplified protocol is that retrieval of the jailed balloon might leave a "gap" (malapposition) between the struts and vessel wall. A previous study showed that OCT could conveniently be acquired from silicon bifurcation phantoms, and OCT had quite strong resolution power to recognize malapposition (27). Therefore, this silicon bifurcation phantom is suitable for testing the reliability of the simplified protocol.…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral arterial diseases (PAD) are developing into an expanding field for endovascular interventions using bioresorbable stents [12], bifurcation stenting in PAD is rare. More clinical experience with bifurcation stenting exists in coronary artery lesions, e.g., in vessels of diameters of 2-4 mm [13][14][15][16][17]. Stenting of the main arterial branch and balloon dilatation only of the side branch (so-called Table 1.…”
Section: Discussionmentioning
confidence: 99%